Laser obscuration and infrared emission characteristics of red phosphorus and mg-al based smoke composition - Pham, Dinh Thang; Phan, Duc Nhan; Nguyen, Trung Toan (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: The capability for laser attenuation and infrared (IR) radiation emission is one of the most essential characteristics determining the camouflage effectiveness of multispectral smoke screens on the battlefield. In this study, the effects of red phosphorus and Mg-Al content, the initial mass of the smoke composition, and the relative humidity on the obscuration characteristics of smoke cloud, including the degree of laser attenuation, the mass extinction coefficient, the Yield factor, and the Figure of Merit, were examined. Additionally, the IR emission properties of smoke screens based on RP/Mg-Al were also evaluated. Methods: Laser radiation attenuation was evaluated by comparing the initial laser power to the power measured after passing through the smoke screen. A 1.064 µm, 11.0 mW continuous-wave laser was transmitted through the test chamber and measured with a power meter. The infrared properties of the smoke clouds were analyzed using an SR-5000N spectral radiometer within the 2.5 – 14.0 µm range. Results: The results indicate that increasing the content of red phosphorus, sample masses, and relative humidity enhances the laser obscuration characteristics. Notably, for a 1 m3 smoke chamber, the estimated optimal sample masses are 3.25 g and 2.30 g at 65% and 90% relative humidity, respectively. Furthermore, increasing Mg-Al content enhances IR emission in the β band (3-5 μm), while emission in the γ band (8-14 μm) decreased.   Conclusion: The laser obscuration characteristics of RP/Mg-Al-based smoke compositions can be effectively controlled by optimizing the RP/Mg-Al content and relative humidity levels. Moreover, the RP/Mg-Al-based compositions demonstrate strong IR radiation characteristics, which are also influenced by the content of RP and Mg-Al. Future research should focus on evaluating the obscuration characteristics of RP/Mg-Al-based compositions in the near- and far-IR regions.
Keywords: multispectral smoke; obscuration performance; infrared radiation characteristics; red phosphorus; Mg-Al alloy